Pengaruh Variasi Setil Alkohol dan Cera Alba terhadap Sifat Fisik Lotion Virgin Coconut Oil - Fitri Wahyuni; Wida Ningsih; Yahdian Rasyadi (JURNAL FARMASI DAN MAKANAN, 2024)
One of the cosmetics that is widely used topically is lotion, which consists of two phases that do not mix, and can be stabilized using an emulsifying agent. Cetyl alcohol and cera alba have properties as softeners, emulsifiers and absorb water which were chosen as emulsifying agents because they can improve the texture of the preparation. The aim of this research was to see the effect of varying concentrations of cetyl alcohol and cera alba as emulsifying agents in VCO lotion preparations. The research design in this study was pre-experimental with the lotion formula divided into 4 sample groups with different concentrations of cetyl alcohol and cera alba. Physical property tests carried out include organoleptic tests, pH tests, homogeneity tests, spreadability tests and lotion type. The results showed that variations in the concentration of cetyl alcohol and cera alba did not show differences in organoleptic, homogeneity, pH, spreadability and type of lotion for all formulas. It can be concluded that in making VCO lotion with varying concentrations of cetyl alcohol and cera alba it does not affect the physical properties of the lotion